Hubungan Strategi Koping dengan Tingkat Stres pada Ibu Primipara Pasca Melahirkan - Atikah, Nurul; Lestari, Widia; Dewi, Yulia Irvani (Universitas Pahlawan Tuanku Tambusai, 2024)
After childbirth, a woman undergo significant changes, requiring them to adapt to their new role as mothers. Failure to adapt can lead them to psychological stress. Coping strategies such as problem focused coping (PFC) and emotional focused coping (EFC), are methods used by mothers to manage the stress. The choice of coping strategy significantly influences the level of stress experienced. The purpose is to determine the correlation between coping strategies and stress levels in postpartum primiparous mothers. The method uses a type of quantitative research using a cross-sectional study approach, consisted of 67 postpartum primiparous mothers, selected using purposive sampling techniques. The results of the study using Spearman Rank showed a significant negative correlation between PFC and stress levels (p-value = 0.001), with a correlation value of -0.412. This indicates that higher PFC values are associated with lower stress levels. Conversely, there was a significant positive correlation between EFC and stress levels (p-value = 0.021), with a correlation value of 0.282. This suggests that higher EFC values are associated with higher stress levels. Conclusion there is correlation between coping strategies and stress levels in postpartum primiparous mothers. Specifically, PFC was negatively correlated with stress, while EFC was positively correlated